Green Manufacturing and Environmental Performance: The Mediating Role of Green Supply Chain in Indonesian Consumer Non-Cyclicals Manufacturers (2022-2024) - Gandini, Aulia; Susilowati, Endah; Haryati, Tantina (Jambura Economic Education Journal, 2026)
Environmental performance among Indonesian Consumer Non-Cyclicals manufacturing firms remains heterogeneous despite increasing sustainability pressures. This study examines the effect of green manufacturing on environmental performance and tests whether green supply chain mediates this relationship under the Natural Resource-Based View (NRBV). Using secondary data from sustainability/annual reports and PROPER ratings for 2022-2024, purposive sampling yields 35 firms (105 firm-year observations). Green manufacturing is proxied by electricity consumption (kWh) transformed using min-max normalization and directional reversal (higher score = greener), while green supply chain is measured through disclosure-based scoring across five indicators. The model is estimated using PLS-SEM with bootstrapping. Results show that green manufacturing has a positive and significant effect on environmental performance. However, green manufacturing is significantly associated with green supply chain in a negative direction, and green supply chain has no significant effect on environmental performance. The indirect effect is not significant, indicating no mediating role of green supply chain in the observation period.